The mineralogy of newly formed dust in active galactic nuclei. (1st December 2017) - Srinivasan, Sundar; Kemper, F.; Zhou, Yeyan; Hao, Lei; Gallagher, Sarah C.; Shangguan, Jinyi; Ho, Luis C.; Xie, Yanxia; Scicluna, Peter; Foucaud, Sebastien; Peng, Rita H.T.
Abstract: The tori around active galactic nuclei (AGN) are potential formation sites for large amounts of dust, and they may help resolve the so-called dust budget crisis at high redshift. We investigate the dust composition in 53 of the 87 Palomar Green (PG) quasars showing the 9.7  μ m silicate feature in emission. By simultaneously fitting the mid-infrared spectroscopic features and the underlying continuum, we estimate the mass fraction in various amorphous and crystalline dust species. We find that the dust consists predominantly of alumina and amorphous silicates, with a small fraction in crystalline form. The mean crystallinity is 8 ± 6%, with more than half of the crystallinities greater than 5%, well above the upper limit determined for the Galaxy. Higher values of crystallinity are found for higher oxide fractions and for more luminous sources. Highlights: The mid-IR spectra of active galactic nuclei (AGN) are modelled to obtain information on the dust mineralogy. The dust consists predominantly of oxides and amorphous silicates, with a small fraction in crystalline form. The higher mean crystallinity compared to the Galactic ISM implies that AGN dust has a different composition.